Fluid Phase Behavior of the Licuri (Syagrus coronata) Fatty Acid Ethyl Ester + Glycerol + Ethanol Mixtures at Different Temperatures—Experimental and Thermodynamic Modeling - Toledo, Iza Estevam Pedrosa; Coêlho, Dayana de Gusmão; Meili, Lucas; Hiranobe, Carlos Toshiyuki [UNESP]; Corazza, Marcos Lúcio; Arce, Pedro; da Silva, Erivaldo Antônio [UNESP]; de Carvalho, Sandra Helena Vieira; dos Santos, Renivaldo José [UNESP]; Soletti, João Inácio; Ferreira-Pinto, Leandro [UNESP] (MDPI, 2024)
This study provides experimental insights into the liquid–liquid equilibrium (LLE) of a system consisting of fatty acid ethyl ester (FAEE) derived from licuri oil, glycerol, and ethanol, evaluated at various temperatures and standard atmospheric pressures. FAEE was synthesized through transesterification of licuri oil using NaOH as a catalyst. The liquid phase compositions were assessed via titration, and the results were consistent with the solubility curves and overall compositions. Data reliability was confirmed using Hand and Othmer-Tobias correlations, with a determination coefficient (R2) of 1, validating the dependability of the results. The NRTL model was employed to correlate the LLE data, yielding a root-mean-square deviation (RMSD) of approximately 1.20%, signifying a strong correlation with experimental uncertainties. The selectivity (S) and distribution (D) parameters indicated the efficacy of glycerol in the system, with S values exceeding 1 under all conditions tested. This investigation is crucial for biodiesel production, highlighting the potential of licuri oil as a renewable feedstock and the importance of phase equilibrium studies in the separation processes of biodiesel production products.
Keywords: biodiesel; ethanol; licuri oil; liquid–liquid; nrtl; Syagrus coronata